Magnetic Nanostructures for Biomedical Applications: An Iron Nitride Crystal/Cationic Lipid Nanocomposite for Enhanced Magnetically Guided RNA Interference in Cancer Cells - Namiki, Yoshihisa; Matsunuma, Satoshi; Inoue, Tetsutaro; Koido, Shigeo; Tsubota, Akihito; Kuse, Yoji; Tada, Norio (IntechOpen, 2011)
None